Chronology of the diversification of anurans - (:unkn) unknown (My University, 2022)
Among Lissamphibia, Anura represents the most diverse clade, with more than 7500 species currently recognized, present on almost every continent and environment. This diversity is a result of a long and rich evolutionary history, with molecular clock analyses tracing its origin more than 250 Ma ago. In the fossil record, anurans are present in almost all continents since the Jurassic. However, numerous disparities exist between continents, clades and eras. As such, most African neobatrachian clades still lack a fossil record and their early diversification and evolution are poorly known. Even the early diversification of Pipidae, an endemic African and South American clade, is poorly documented in both continents. Thus, the evolutionary history of Anura is not known in detail, with numerous gaps in it. In peculiar, most of the early diversification of African extant clades, like Pipidae and Neobatrachia, remains cryptic. Hence, this hinders efforts to reconstruct the paleobiogeographical evolution of this clade, and assess the impact of the extinction crises on them. The objectives of this dissertation are to improve our understanding of anuran diversification through the study of the early diversification of African neobatrachians and Pipidae during the Mesozoic and Paleogene.This study focuses on two African sites, the Kem Kem Formation from the Late Cretaceous of Morocco, and In Becetén, from the Late Cretaceous of Niger, where both pipids and neobatrachians have been mentioned, but never described in detail. In addition, the exceptional preserved ranoid Thaumastosaurus, from the Eocene of Western Europe, is also studied, as previous reports suggested that it could be related to endemic African ranoids. The study of the anurans from In Becetén reveals the most diverse site of Mesozoic Africa, with at least 7 anuran taxa identified, including 4 pipimorphs and likely two neobatrachians, showing that both clades were already diverse by the middle Lat
Keywords: African Research